Analisis Manajemen Operasional Dan Persediaan Bahan Baku Terhadap Produksi Di Zocha Graha Kriya - Sutisnawati, Yayah; Rifania, Regina Rizki; Muthmainah, Minda; Rahman, Alif Dzakir; Alif, Reyhan Mochammad (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2024)
The purpose of this study was to determine which strategy should be used by Garut MSMEs. The analysis method used is a descriptive qualitative analysis method using SWOT (Strengths, Weaknesses, Opportunities, Threats), IFAS (Internal Factor Analysis Summary), EFAS (External Factor Analysis Summary), and IE (Internal External). The results of this analysis examine the company's internal environment, namely strengths and opportunities, and the company's external environment, weaknesses and threats. The total value of the entire internal section in the IFAS matrix analysis and the external section in EFAS has points above average. When analyzing the SWOT matrix, the most points were obtained in the Weakness Opportunities (WO) approach. After analyzing using the Internal External (IE) matrix method, the results showed the position of Garut MSMES in column I, which indicates that it is in a strong or dominant position, and the external environment analysis is in a strong position. This position indicates that Zocha Graha Kriya MSMEs has aggressive growth. The approach that can be used is the Weakness Opportunities (WO) approach, which optimizes existing strengths and pays attention to market opportunities. This approach must be assisted by efforts to develop production efficiency (increase production efficiency), qualified human resources, technology integration, and building partnerships. Based on the SWOT, IFAS, EFAS, and IE analysis, Garut MSMEs has a strong position in the internal and external environment. The recommended strategy is WO (weakness opportunities), focusing on internal strengths and market opportunities. Efforts are needed to increase production efficiency, develop human resources, integrate technology, and form partnerships.